Emotional regulation and resilience of students writing thesis in higher education - Nurfarhanah Nurfarhanah; Azmi Ade Karina (Universitas Negeri Padang, 2023)
This research delves into the psychological aspects of students undertaking thesis writing, specifically focusing on how they handle emotional challenges and build resilience during this demanding academic process. The study encompasses a diverse group of 162 students from the 2018 intake at a university in Padang, selected through a simple random sampling method. To ensure a comprehensive analysis, the study employs a blend of correlation, regression, and descriptive analytics, adhering to a statistical significance threshold of 0.05. The primary data for this research was processed using the SPSS 16.0 software. This included conducting the Kolmogorov-Smirnov test to assess the normality of data, a linearity test, and the Glesjer test to determine the presence of heteroscedasticity. Two key instruments guided the data collection and analysis: an emotional regulation instrument with a reliability index of 0.68, and a resilience instrument with a higher reliability index of 0.87. These instruments were crucial in measuring the respective constructs. The findings of the study are illuminating. Firstly, it was found that the students generally demonstrated effective emotional regulation skills. Secondly, a high level of resilience was observed among the student participants. Importantly, the correlation tests revealed a significant relationship between resilience and emotional regulation. This implies that the ability to regulate emotions effectively is closely linked to the development of resilience in students. Additionally, the regression analysis presented a substantial impact of emotional regulation on resilience, with a contribution strength of 51.5%. In essence, this study provides valuable insights into the emotional and psychological resilience of students during thesis writing. It highlights the critical role of emotional regulation in fostering resilience, offering a perspective that could be beneficial for academic institutions and mental health professionals in supporting students through their academic journeys.